The scenario will will be represented by: ![x+x+2x+4x=-104](https://tex.z-dn.net/?f=x%2Bx%2B2x%2B4x%3D-104)
The number will be -13
Step-by-step explanation:
We have to convert the given situation into the mathematical form
Let x be the number
Then
"a number plus itself"
x+x
"plus twice itself"
x+x+2x
"plus 4 times itself"
x+x+2x+4x
"is equal to -104"
![x+x+2x+4x=-104](https://tex.z-dn.net/?f=x%2Bx%2B2x%2B4x%3D-104)
This can also be written as:
![x+x+2x+4x=-104\\8x=-104\\Dividing\ both\ sides\ by\ 8\\\frac{8x}{8}=\frac{-104}{8}\\x=-13](https://tex.z-dn.net/?f=x%2Bx%2B2x%2B4x%3D-104%5C%5C8x%3D-104%5C%5CDividing%5C%20both%5C%20sides%5C%20by%5C%208%5C%5C%5Cfrac%7B8x%7D%7B8%7D%3D%5Cfrac%7B-104%7D%7B8%7D%5C%5Cx%3D-13)
Keywords: Linear Equation
Learn more about linear equation at:
#LearnwithBrainly
The value of dividing x^2-3x+9 by x-2 is x + 3
<h3>Ways of dividing polynomials</h3>
There are several ways to divide polynomial functions; some of these ways include
- By factorization
- By long division
- By synthetic division
- By using technology such as graph
<h3>How to divide the polynomials?</h3>
The expression for the polynomial division is given as:
x^2-3x+9/x-2
To divide polynomial functions, we make use of the division by factorization method
Start by expanding the numerator of the polynomial division
x^2-3x+9/x-2 = x^2 + 3x - 6x + 9/x-2
Factorize the equation
x^2-3x+9/x-2 = x(x + 3) - 2(x + 3)/x - 2
Factor out x + 3 from the numerator
x^2-3x+9/x-2 = (x- 2)(x + 3)/x - 2
Cancel out the common factors
x^2-3x+9/x-2 = x + 3
Hence, the value of dividing x^2-3x+9 by x-2 is x + 3
Read more about polynomial division at:
brainly.com/question/25289437
#SPJ1
27^1/3= a number you multiply by itself three times to get 27
Cubic root of 27 is 3
= 3
Answer:
the factors of x^3-1 are ![x^3 -1 = (x-1) (x^2 +x+1)\\](https://tex.z-dn.net/?f=x%5E3%20-1%20%3D%20%28x-1%29%20%28x%5E2%20%2Bx%2B1%29%5C%5C)
Step-by-step explanation:
We need to find factors of x^3 -1
![x^3-1 \\(x)^3 -(1)^3\\We \,\, know\,\, a^3 -b^3 = (a-b) (a^2 +ab + y^2) \\So, \,\, using\,\, the \,\, formula\,\,\\Here\,\, a= x \,\,and\,\, b= 1\\(x)^3 -(1)^3 = (x-1) (x^2 +x+1)\\](https://tex.z-dn.net/?f=x%5E3-1%20%5C%5C%28x%29%5E3%20-%281%29%5E3%5C%5CWe%20%5C%2C%5C%2C%20know%5C%2C%5C%2C%20a%5E3%20-b%5E3%20%3D%20%28a-b%29%20%28a%5E2%20%2Bab%20%2B%20y%5E2%29%20%5C%5CSo%2C%20%5C%2C%5C%2C%20using%5C%2C%5C%2C%20the%20%5C%2C%5C%2C%20formula%5C%2C%5C%2C%5C%5CHere%5C%2C%5C%2C%20a%3D%20x%20%5C%2C%5C%2Cand%5C%2C%5C%2C%20b%3D%201%5C%5C%28x%29%5E3%20-%281%29%5E3%20%3D%20%28x-1%29%20%28x%5E2%20%2Bx%2B1%29%5C%5C)
So, the factors of x^3-1 are ![x^3 -1 = (x-1) (x^2 +x+1)\\](https://tex.z-dn.net/?f=x%5E3%20-1%20%3D%20%28x-1%29%20%28x%5E2%20%2Bx%2B1%29%5C%5C)
4.4 is greater because the tenths place (4) is higher than the other number's tenth place (0).